2018
DOI: 10.21577/0100-4042.20170190
|View full text |Cite
|
Sign up to set email alerts
|

Utility of Functionalized Agarose Nanoparticles in Hydrolyzing Lactose in Batch Reactors for Dairy Industries

Abstract: The present study investigates the synthesis of agarose nanoparticles (ANPs) and its surface modification by galactose for the immobilization of β-galactosidase. Galactose modified ANPs retained 91% enzyme activity upon immobilization. Optimum pH (4.5) and temperature (50 °C) remains unchanged after immobilization. However, immobilized enzyme retained greater catalytic activity against lower and higher, pH and temperature ranges. Immobilized β-galactosidase retained 89% biocatalytic activity even at 4% galacto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…inhibitor binding site in β-galactosidase that promotes the reduction in inhibition as a result of the support to the inhibitor's access to the binding site (Kim et al, 2011;Ansari et al, 2018). Our study suggested that GCNPs-βG showed 71% activity even after 1 hour at 5% galactose concentration.…”
Section: Stability In Various Ranges Of Ph and Temperaturementioning
confidence: 63%
See 3 more Smart Citations
“…inhibitor binding site in β-galactosidase that promotes the reduction in inhibition as a result of the support to the inhibitor's access to the binding site (Kim et al, 2011;Ansari et al, 2018). Our study suggested that GCNPs-βG showed 71% activity even after 1 hour at 5% galactose concentration.…”
Section: Stability In Various Ranges Of Ph and Temperaturementioning
confidence: 63%
“…The free enzyme showed 56% activity at pH 6.0 while β-galactosidase immobilized on CNPs, carboxylated CNPs and glutaraldehyde-modified CNPs retained 69%, 75% and 84%, activity, respectively, under similar conditions. It could be due to greater alteration/ distortion produced in the tertiary structure of the free enzyme in highly acidic and basic solutions than that of the immobilized enzyme (Ansari et al, 2018). Figure 4 suggests that the temperature-optima was 50 o C for soluble and immobilized enzyme preparations.…”
Section: Stability In Various Ranges Of Ph and Temperaturementioning
confidence: 99%
See 2 more Smart Citations
“…Wang and Wu [26] described the fabrication of agarose hydrogel nanoparticles using an emulsion-converted-to-suspension method and the application of the obtained particles for encapsulating proteins and peptides. Similar particles were used as batch reactors in dairy industry for the hydrolysis of lactose [27]. Furthermore, many works deal with the fabrication of hybrid metal-agarose particles for combining the electronic properties of metals and the biocompatibility of the agarose to obtain particles with application as biosensors [28,29].…”
Section: Introductionmentioning
confidence: 99%